Leptin and adiponectin regulate the activity of nuclei involved in sleep-wake cycle in male rats - Ramírez-Plascencia, Oscar Daniel; Saderi, Nadia; Cárdenas-Romero, Skarleth; García-García, Fabio; Peña-Escudero, Carolina; Flores-Sandoval, Omar; Azuara-Álvarez, Lucia; Báez-Ruiz, Adrián; Salgado-Delgado, Roberto (Frontiers in Neuroscience, 2022)
Epidemiological and experimental evidence recognize a relationship between sleep-wake cycles and adiposity levels, but the mechanisms that link both are not entirely understood. Adipose tissue secretes adiponectin and leptin hormones, mainly involved as indicators of adiposity levels and recently associated to sleep. To understand how two of the main adipose tissue hormones could influence sleep-wake regulation, we evaluated in male rats, the effect of direct administration of adiponectin or leptin in the ventrolateral preoptic nuclei (VLPO), a major area for sleep promotion. The presence of adiponectin (AdipoR1 and AdipoR2) and leptin receptors in VLPO were confirmed by immunohistochemistry. Adiponectin administration increased wakefulness during the rest phase, reduced delta power, and activated wake-promoting neurons, such as the locus coeruleus (LC), tuberomammillary nucleus (TMN) and hypocretin/orexin neurons (OX) within the lateral hypothalamus (LH) and perifornical area (PeF). Conversely, leptin promoted REM and NREM sleep, including increase of delta power during NREM sleep, and induced c-Fos expression in VLPO and melanin concentrating hormone expressing neurons (MCH). In addition, a reduction in wake-promoting neurons activity was found in the TMN, lateral hypothalamus (LH) and perifornical area (PeF), including in the OX neurons. Moreover, leptin administration reduced tyrosine hydroxylase (TH) immunoreactivity in the LC. Our data suggest that adiponectin and leptin act as hormonal mediators between the status of body energy and the regulation of the sleep-wake cycle.